Superfluid density and two-component conductivity in hole-doped cuprates - Ayres, Jake; Katsnelson, Mikhail I.; Hussey, Nigel E. (Frontiers in Physics, 2022)
While the pseudogap dominates the phase diagram of hole-doped cuprates, connecting the antiferromagnetic parent insulator at low doping to the strange metal at higher doping, its origin and relation to superconductivity remains unknown. In order to proceed, a complete understanding of how the single hole – initially localized in the Mott state – becomes mobile and ultimately evolves into a coherent quasiparticle at the end of the superconducting dome is required. In order to affect this development, we examine recent transport and spectroscopic studies of hole-doped cuprates across their phase diagram. In the process, we highlight a set of empirical correlations between the superfluid density and certain normal state properties of hole-doped cuprates that offer fresh insights into the emergence of metallicity within the CuO2 plane and its influence on the robustness of the superconducting state. We conclude by arguing that the overall behavior is best understood in terms of two distinct current-carrying fluids, only one of which dominates the superconducting condensate and is gapped out below the pseudogap endpoint at a critical hole concentration p∗.